ETIKA PUBLIK DALAM TRANSISI ENERGI BERSIH: DILEMA MORAL PENGEMBANGAN PANAS BUMI DI PULAU FLORES - Rizhard Anselmus Ndolu; Henda Taopan; Noni Banunaek (Journal of Technology and Engineering, 2026)
Indonesia’s transition toward clean energy faces complex ethical dilemmas, particularly in the context of geothermal energy development on Flores Island. Through the Flores Geothermal Island policy, the government seeks to position Flores as a national laboratory for clean energy. However, behind the narrative of a low-carbon energy transition, social and moral tensions have emerged among the state, corporations, and Indigenous communities. This study employs a descriptive qualitative approach based on document analysis and ethical interpretivism to examine the relationship between social legitimacy, ecological justice, and public ethics in geothermal energy governance. The findings indicate the dominance of an economic utilitarian paradigm in national energy policy (40%), with a primary emphasis on efficiency and investment, while the values of ecological justice (30%), public ethics and participation (20%), and local spirituality (10%) remain marginalized. This imbalance reflects a deficit of public ethics in the clean energy transition process on Flores Island. The study highlights the need for a transformation of public ethics in energy policy, shifting from a technocratic orientation toward a paradigm grounded in social, ecological, and spiritual justice. Accordingly, clean energy should be understood not merely as a technological project but also as a moral project that respects both humanity and nature.